PENGARUH PENDIDIKAN KESEHATAN DENGAN AUDIO VISUAL TERHADAP PERILAKU CUCI TANGAN PAKAI SABUN ANAK PRA SEKOLAH - Dwi Aprilina Adriani; Ni Made Aries Minarti; Dian Adriana (Coping: Community of Publishing in Nursing, 2014)
Preschool is the golden age, which in this stage children are able to think concrete and real. Audio visual media is one method of learning about hand washing in preschool. The aim of this study is to determine the effect of health education with audio visual on behavior of  hand washing by soap in preschool in PAUD Aisyiah Dalung in 2013. This research is pre-experiment by pre-post test design with 33 samples of children which is used total sample. The collecting data by giving questionnaire and observation sheet. All children are given health education with audio visual six sessions for 15-30 minutes. The result showed 3 children (9,1%) misbehave, 30 children (90,9%) have quite well behaved and there is not good behavior on hand washing by soap before it is given the health education with audio visual and after given the health education it showed 33 children (100%) well behaved. Based on Wilcoxon Signed Rank Test obtained p value = 0,001 that means there are health education with audio visual effected behavior of hand washing by soap in preschool in PAUD Aisyiah Dalung in 2013. From this research suggested for educational institutions in order to provide specific health education schedules and facilities for hand washing.